Asymptotic Theory for Local Time Density Estimation and Nonparametric Cointegrating Regression - Wang, Q. Y. (Institutional Knowledge at Singapore Management University, 2009)
Asymptotic theory is developed for local time density estimation for a general class of functionals of integrated and fractionally integrated time series. The main result provides a convenient basis for developing it limit theory for nonparametric cointegrating regression and nonstationary autoregression. The treatment directly involves local time estimation and the density function of the processes under consideration, providing an alternative approach to the Markov chain and Fourier integral methods that have been Used in other recent work on these problems.